(untitled) (Research, Society and Development, 2026)
The identification of individuals with Giftedness constitutes a complex and multifactorial assessment process involving cognitive, educational, and often unobserved nuances. The difficulty in defining and measuring what giftedness is results from its complex nature and the absence of a consensus on scientific criteria, representing a central and intensifying challenge to the precision of the assessment process. Based on the discussed problematic, this study is a scoping review of an exploratory and descriptive nature, focusing on mapping the main challenges present in the neuropsychological assessment of children and adolescents with giftedness, answering the question: “What are the challenges faced in the neuropsychological assessment of children and adolescents for the diagnosis of High Ability/Giftedness?”. The search for evidence was conducted on the Web of Science database, using scientific articles published between 2020 and 2024, in Portuguese, English, and Spanish. The studies were selected and data were extracted by the team of authors, in a paired process. The challenges found were organized into topics: High Relevance of Intelligence Quotient, Socioeconomic Issues, Single Assessment, Diffuse Criteria, and Twice-Exceptionality. The results reflect challenges indicative of major impasses due to a lack of consensus in the scientific community. This not only hinders access to standardized and quality assessment for those who need it, but also limits the implementation of adequate and effective interventions.